2014
DOI: 10.3171/2013.12.jns132092
|View full text |Cite
|
Sign up to set email alerts
|

Hockey Concussion Education Project, Part 3. White matter microstructure in ice hockey players with a history of concussion: a diffusion tensor imaging study

Abstract: Object The aim of this study was to examine the brain’s white matter microstructure using magnetic resonance diffusion tensor imaging (DTI) in ice hockey players with a history of clinically symptomatic concussion compared to those players without a history of concussion. Methods Sixteen players with a history of concussion (Concussed Group; mean age: 21.7 ± 1.5 years; 6 female) and eighteen players without a history of concussion (Non-Concussed Group; mean age: 21.3 ± 1.8 years, 10 female) underwent 3T DTI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 46 publications
5
51
0
Order By: Relevance
“…53 Collegiate ice hockey players exhibited similar white matter changes over the course of a season. [54][55][56][57] In addition, repetitive subconcussive head impacts in collegiate American football players have been linked, in a dose-dependent manner, to deficits in BBB integrity, potential loss of white matter integrity, and cognitive dysfunction. 58 These findings probably reflect some level of risk for youths who sustain repetitive subconcussive head impacts, although little research has been devoted specifi cally to this topic.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…53 Collegiate ice hockey players exhibited similar white matter changes over the course of a season. [54][55][56][57] In addition, repetitive subconcussive head impacts in collegiate American football players have been linked, in a dose-dependent manner, to deficits in BBB integrity, potential loss of white matter integrity, and cognitive dysfunction. 58 These findings probably reflect some level of risk for youths who sustain repetitive subconcussive head impacts, although little research has been devoted specifi cally to this topic.…”
Section: Subconcussive Blowsmentioning
confidence: 99%
“…Clinical neuroimaging studies, including conventional MRI, are normal in the majority of cases. 17 For this reason, authors of recent studies have aimed to apply even more sophisticated neuroimaging techniques to this condition, including magnetoencephalography, 53 diffusion tensor imaging (DTI), 11,25,29,31,44,47 and task-based functional MRI (fMRI). 7,26,35,49 Despite detecting changes between groups of concussion patients and healthy controls, none of these techniques has emerged as a useful clinical tool that contributes to the management of acute SRC or PCS.…”
mentioning
confidence: 99%
“…Whereas some recent studies have indicated a correlation between cognitive measures and functional [39,42,[48][49][50] or structural neuroimaging data [16,17,24,26,28], other studies have failed to do so [15,19,30].…”
Section: Correlations Of Dti Metrics and Resting State Data With Cognmentioning
confidence: 92%
“…Although the number of published studies using DTI has more than quadrupled since 2002 [12], the utility of DTI for assessing white matter tract injury in concussion is still unclear. Several recent DTI studies have reported either high [13][14][15][16][17][18][19] or low [18,[20][21][22][23][24][25][26] FA following concussion, and one longitudinal study has shown both increases as well as decreases of anisotropy within the same individual over time [18] (see Table 1). These disparate findings in the recent concussion literature have spurred the hypothesis that anisotropic differences in concussed patients could differ depending on whether the patient is imaged immediately after the concussion or months/years postconcussion [13,14].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 94%